An interesting presentation of acute liver failure in pregnancy - a case report. (18th April 2012) - Alzouebi, A; Syed, S; Horner, E; Amin, T
Abstract : Acute liver failure in pregnancy is associated with significant morbidity and mortality. Often it can be challenging to diagnose and manage. This can be as a result of overlapping symptoms and signs of conditions specific to pregnancy related liver disease such as, obstetric cholestasis, pre-eclampsia and acute fatty liver.1 Acute fatty liver (AFL) of pregnancy and Obstetric cholestasis typically occurs in the third trimester. We present a case of a 31year old, Asian primigravida, whom presented with itching at 30 weeks gestation. Investigations revealed normal liver ultrasound scan, negative hepatitis screen, and normal bile acids and raised ALT of 116. A diagnosis of obstetric cholestasis was made. At 37 weeks gestation, the patient went on to develop significant pre-eclampsia and was delivered by emergency caesarean section. Immediately post delivery the patient developed acute liver and renal failure with persistent hypoglycaemia. A diagnosis of acute hepato-renal failure was made. The patient went on to make a full recovery. This case highlights the potential catastrophic sequelae to mother and newborn with acute liver disease. Prompt diagnosis, early involvement of a multi-disciplinary team and management in a critical care unit is vital for good prognosis.